Gastric mucosal perfusion in dogs: Effects of halogenated anesthetics and of hemorrhage - Evangelista Silva, Alexandre [UNESP]; Do Nascimento, Paulo [UNESP]; Lilian Beier, Suzane [UNESP]; Matheus Roberto, Wellington [UNESP]; Braz, Leandro Gobbo [UNESP]; Antonio Vane, Luiz [UNESP]; Marisa Ganem, Eliana [UNESP]; Braz, José Reinaldo Cerqueira [UNESP] (Taylor & Francis Inc, 2008)
The gastrointestinal tract is one of the first organs affected by hypoperfusion during hemorrhagic shock. The hemodynamics and oxygen transport variables during hemorrhagic shock and resuscitation can be affected by the anesthetics used. In a model of pressure-guided hemorrhagic shock in dogs, we studied the effects of three halogenated anesthetics - halothane, sevoflurane, and isoflurane - at equipotent concentrations on gastric oxygenation. Thirty dogs were anesthetized with 1.0 minimum alveolar anesthetic concentration (MAC) of either halothane, sevoflurane, or isoflurane. A gastric tonometer was placed in the stomach to determine mucosal gastric CO2 (PgCO(2)) and for the calculation of gastric-arterial PCO2 gradient (PCO2 gap). The dogs were splenectomized and hemorrhaged to hold mean arterial pressure at 40-50 mm Hg over 45 min and then resuscitated with the shed blood volume. Hemodynamics, systemic oxygenation, and PCO2 gap were measured at baseline, after 45 min of hemorrhage, and at 15 and 60 min after blood resuscitation. Hemorrhage induced reductions of mean arterial pressure and cardiac index, while systemic oxygen extraction increased (p < .05), without significant differences among groups (p > .05). Halothane group showed significant lower PCO2 gap values than the other groups (p < .05). After 60 min of shed blood replacement, all groups restored hemodynamics, systemic oxygenation, and PCO2 gap to the prehemorrhage levels (p > .05), without significant differences among groups (p > .05). We conclude that halothane is superior to preserve the gastric mucosal perfusion in comparison to isoflurane and sevoflurane, in dogs submitted to pressure-guided hemorrhagic shock at equipotent doses of halogenated anesthetics.
Keywords: gastric gas tonometry; hemorrhagic shock; halogenated anesthetics; halothane; isoflurane; sevoflurane